The Christmas oratorio in vocal score with a separate accompaniment for the organ or pianoforte - BACH, Johannes Sebastian (Novello and Company, 1951)
Christians, be joyful, Now it came to pass, See now the bridegroon, Prepare thyselt Zion, How shall I fitly meet Thee, Ah ! dearest Jesus, And the Angel said, Haste ye shepherds, Glory to God in the highest, With all Thy hosts, Hear King af Angels, And when the Angels, Rejoice and sing,